Patterns of tertiary prophylaxis in Canadian adults with severe and moderately severe haemophilia B. (3rd March 2014) - Jackson, S. C.; Yang, M.; Minuk, L.; St‐Louis, J.; Sholzberg, M.; Card, R.; Iorio, A.; Poon, M.‐C.
Summary From a young age patients with severe and moderately severe FIX deficiency (haemophilia B) can experience spontaneous or traumatic bleeding and joint destruction may result. The use of coagulation factor IX concentrate to prevent anticipated bleeding, as primary or secondary prophylaxis, has become a common and recommended practice in children. The current practice of using tertiary prophylaxis, in the presence of established joint arthropathy, in adults with haemophilia B is not well characterized. This observational study was conducted to gain a better understanding of the recent Canadian experience with tertiary prophylaxis in adults with severe and moderately severe haemophilia B. Data were collected from all eligible adult (≥ 18 years of age) males with baseline FIX:C ≤ 2% from seven Canadian Hemophilia Treatment centres over a 2‐year observation period from 2009 to 2011. Thirty‐four per cent of the 67 subjects with moderately severe haemophilia B were exposed to prophylaxis with the majority as continuous prophylaxis (≥45 weeks year‐1). The severe subgroup (FIX:C < 1%) demonstrated a 52% exposure rate. None had primary prophylaxis exposure in childhood. Eighty‐one per cent used once or twice weekly infusion regimens and reported a median annual bleeding rate of five bleeds per year versus four bleeds per year for those using on‐demand treatment. Annual median factor utilization for all subjects using prophylaxis was 196 283 U year‐1 compared to 46 361 U year‐1 for on demand. Approximately 50% of adults with severe haemophilia B are using continuous tertiary prophylaxis in Canada, a practice likely to increase which warrants further study.